EPIZOOTIC DATE OF PANLEUKOPENIA IN CATS AND COMPARATIVE EVALUATION OF TREATMENT SCHEMES IN LLC "BIOCENTR" POLTAVA CITY - Коне, М. С.; Корчан, Л. М.; Петренко, А. А.; Опришко, А. Л. (Scientific Progress & Innovations, 2014)
Age and breed sensitivity, seasonal occurrence and display dynamics of panleukopenia in cats in the conditions of veterinary clinics of LLC "Biocentr" Poltava city have been studied. Offered a variety of treatment regimens of panleukopenia in cats. A new treatment regimens of panleukopenia in cats was developed. It was descorvered, that panleukopenia often recorded among cats aged from two months to one year. More prone to disease without-breed animals. The disease has a seasonal expression, manifested frequent case of panleukopenia in the spring-summer-autumn period. The proposed treatment regimen provides one hundred percent therapeutic effiectivity.